Corporate governance, earnings quality and the effect on cost of capital. - Lim, Chin Ling. (2008)
We explore the moderating effect of firm-specific corporate governance- independence and frequency of meetings of Board of Directors and Audit committee- on the relationship between cost of capital and earnings quality